2013
DOI: 10.4314/tjpr.v12i3.25
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacists’ Perception of the Relevance of Drug Package Insert as Source of Drug Information in Southwestern Nigeria

Abstract: Purpose: To evaluate the opinions of community pharmacists on the usefulness and reliability of drug package inserts (DPI) as drug information source, and necessary modifications needed to improve their contents. Methods: A prospective cross-sectional study using a pretested questionnaire was administered to sixty-one superintendent community pharmacists (CP) across two cities in southwestern Nigeria. Descriptive statistics was used to summarize the data and evaluate respondents' opinion. Kruskal-Wallis test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…A study done in Nigeria reported that majority of pharmacists ( N = 42; 72.8%) believe that information from drug package inserts was precise and used it as a reference [19]. A similar belief and easy availability might be attributed to the high use of drug package inserts as drug information resources in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…A study done in Nigeria reported that majority of pharmacists ( N = 42; 72.8%) believe that information from drug package inserts was precise and used it as a reference [19]. A similar belief and easy availability might be attributed to the high use of drug package inserts as drug information resources in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…Pharmacists in Japan considered that existing drug leaflets require modification to be of use to patients [ 151 ], and few used them to help their communications with patients [ 152 ]. Similarly, pharmacists in Nigeria considered that the PIs provided with medicines need changes to make them patient-friendly [ 153 ]. Many doctors surveyed in Sudan did not recommend patients read PIs, despite perceiving a need to provide information, in part because many were not written in the local language [ 154 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gelayee et al reported that DI centers were "never" consulted by 70.8% of the respondents [12]. Some of the results of foreign studies were compatible with outcomes for DI centers from 14,8% to 29.2% [12,23] however higher preferences were also pronounced by Hennigen and Chan [22,25]. In Rae's study, DI centers were in the 6th rank [5].…”
Section: Discussionmentioning
confidence: 83%
“…In other studies, only Diobi's study exceeded this rate with 98.4%, while in Gelayee's and Al Tabakha's studies disagreeing with 39% and 13.9%, respectively [12,16,23]. Although those sources are always available in the pharmacy setting, the currency, appropriateness, and responsiveness are controversial since some changes might have been realized during the elapsed time from releasing to the market and the given time to reach the pharmacy [24].…”
Section: Discussionmentioning
confidence: 87%